Contribution of Haji Abdul Latif Syakur in Modernizing Islamic Education - Nofa, Yosi; Jie, Lie (Yayasan Minang Darussalam, 2023)
Haji Abdul Latif was an important figure in Islamic reform in the 20th century. In the matter of education, he views that education is the right of every human being according to the needs of human development itself without differentiation of gender and knowledge. This article aims to explain the thoughts of Haji Abdul Latif Syakur in the field of education. The primary data of this research is a manuscript by Haji Abdul Latif Syakur. The manuscript is read with historical and sociological approaches. The results of data analysis show that Haji Abdul Latif Syakur was the first ulama to reform education by modernizing the learning system and curriculum, namely in 1906, three years before Islamic modernists. In addition, since he first taught Islam in 1904, he has taught and involved women in the learning process.